Emotion regulation in adolescents with acne vulgaris: correlates of medication adherence, clinical dimensions and psychopathology symptoms: a cross-sectional study - Turan, Serkan; Turan, Işıl Kamberoğlu; Özbağcıvan, Özlem (The Turkish Journal of Pediatrics, 2020)
Background. Acne vulgaris causes profound negative physical, psychological and social effects on self-image and a negative impact on the quality of life. Most research so far has been limited to adults, and little is known about the emotion regulation, medication adherence, clinical dimensions and psychopathology symptoms in young people with acne vulgaris. Methods. A cross-sectional analytical study was conducted in a center in western Turkey. Ninety-six adolescents with acne vulgaris and 100 controls participated in the study. All participants completed self-report questionnaires including the Strength and Difficulties Questionnaire (SDQ), Difficulties in emotion regulation scale (DERS) and Morisky medication adherence scale-8 (MMAS-8). Acne severity was assessed with The Global Acne Grading Score (GAGS). Results. Acne vulgaris patients showed poorer SDQ and DERS scores reflecting the emotional regulation problems and psychopathological symptoms compared to healthy controls. The percentages of high, medium and low adherence were 6%, 36% and 58% for oral medication; and 17.39%, 56.52% and 26.09% for topical medication, respectively. There were significant correlations between all SDQ subscale scores and the scores for the impulsivity subscale and total scores of DERS. A statistically significant positive correlation was found between MMAS-8 and the choice of topical/oral medication. Likewise, GAGS were correlated with three specific SDQ domains: emotional symptoms, prosocial behavior and total scores, and with three specific DERS domains: clarity, strategy and total scores. Conclusions. Maladaptive emotion regulation strategies of patients with acne vulgaris may be associated with higher psychopathological symptoms and lower beliefs in treatment efficacy. It is important to include emotional regulation interventions to improve medication adherence and quality of health care in young acne patients.
Keywords: Difficulties in emotion Regulation Scale; acne vulgaris; adolescent; medication adherence; psychopathological profile